Implementation of Corporate Social Responsibility Based on Triple Bottom Line Concepts on the Company’s Financial Performance: Empirical Studies in Manufacturing and Mining Companies - Hilmi, Hilmi; Zarkasyi, Wahyudin; Sueb, Memed; Tanzil, Nanny Dewi (International Journal of Economics and Financial Issues, 2021)
The purpose of this study is to examine how the influence of corporate social responsibility performance on corporate financial performance which is measured by the concept of 3P (Profit, People, Planet) seen from the company’s sustainability report while the company’s financial performance is measured by using ratio finance (current ratio, debt to equity ratio, total assets turnover, and return on equity). The population used in this research is manufacturing and mining company in BEI Year 2013-2018, the sample taken is companies that publish financial statements, annual reports, sustainability reports or corporate social responsibility reports that can be accessed through the company website or on the website of BEI (www.idx.co.id). Research findings indicate that the performance of corporate social responsibility affects the financial performance of the manufacturing and mining companies. Keywords: Triple Bottom Line, mining companies, manufacturing companies, Financial Performance. JEL Classifications: G2, M14 DOI: https://doi.org/10.32479/ijefi.11190